Acreage Response and Price Fluctuation of Rice in Bangladesh - Khalique, Md Forhed Bin; Moniruzzaman, Md; Touhiduzzaman, Sarker Md; Islam, Md Shahidul; Murmu, Hilarius; Rozario, Elizabeth; Rashid, Md Harun Or (International Journal of Pure Agricultural Advances, 2019)
The aim at the study is to examine the annual price fluctuation, and acreage response of rice in Bangladesh using the time series data for the period 1981-82 to 2010-11. Acreage response was estimated within the Nerlovian Partial Adjustment Model. The study estimates the growth rate of the area, production, yield and nominal price of rice and annual fluctuation on nominal and real prices of all the three rice seasons. The study was based on secondary data. Price fluctuation of Aus rice for nominal and real price was highest (-26.6 to 46.9) and (-29.4 to 37.2) in sub-period II (1991-92 to 2000-01). The fluctuation in nominal and real price of Aman rice was also highest (-27.0 to 40.7) and (-29.7 to 29.2) in the sub-period II (1991-92 to 2000-01). The fluctuation in nominal and real Boro rice price was also highest (-48.5 to 28.5) and (-34.4 to 28.4) in the sub-period II (1991-92 to 2000-01). Growth rates of area, production, yield and nominal price of three seasons of rice were estimated by fitting exponential trend function. Growth rates of area which were significantly negative for Aus, Aman that were -4.6 percent and -0.3 percent and positive for Boro rice it was 4.5 percent over the whole period. The growth rates of yield for Aus, Aman, and Boro were increased significantly at the rate of 2.2, 1.9 and 1.9 percent respectively during the entire time period. Farmer’s field-oriented policy should be developed for high yield and stable market.